Evaluation of photoperiod sensitivity and adaptation in Kenaf (Hibiscus cannabinus) in some Nigerian agro-ecologies (2012)
Seven genotypes of Kenaf were grown in pots at controlled and natural photoperiod (PP) regimes in Ibadan, South-western Nigeria, to determine their PP sensitivities. Numbers of days to flowering and fibre yield were recorded. The same genotypes were grown on the field at Jos, Ibadan and Badeggi of high altitude, southern guinea savannah and forest agro-ecologies of Nigeria, respectively. Days to flowering, fibre and seed yields were recorded. Potted plants grown at natural PP flowered earliest, 54 days after planting (DAP) while they flowered at 118 DAP at 12 hours PP. IFEKEN DI400flowered 20 days later than other genotypes at both PP regimes, and was grouped as being relatively photo- insensitive. Fibre yield was significantly higher at natural than at 12 hours PP only in IFEKEN DI400, with highest mean yield of24.08g / plant. In the genotype x environment studies, IFEKEN DI400 was consistently latest to flower across locations with an average of 107 days. Mean fibre yield of 11,314.5kg/ha in Ibadan tripled that obtained in Badeggi and Jos. Genotype Tainung had the highest seed yield of 473.75g and 179.35g at Badeggi and Ibadan, respectively while the lowest seed yield 201.08g for Jos was recorded in genotype 8B. Badeggi is recommended for seed production while Ibadan is recommended for fibre production pending the availability of specifically adapted genotypes. The genotypes IFEKEN DI400, Tainung and 8B are candidate genotypes in breeding for high yield and adaptation to Nigerian agro-ecologies.